# Mass difference between two baryons

I have been trying to make sense out of this (unsuccessfully for days). It's an exercise on Particle Physics. Exercise asks to calculate the mass difference between baryons ($$cuu$$) with $$\begin{equation*} J^p = (3/2)^+ and (1/2)^+ \end{equation*}$$ respectively, by using the operator: $$\begin{equation*} H_{ss} = K \sum_{i

Where $$K$$ is a constant, $$S$$ is the spin operator, and $$m$$ are the masses.

I know beforehand the solution for the operator must be: $$\begin{equation*} H_{ss} =\frac{K}{2 m_u^2}(s(s+1) - \frac{3}{2}) + \frac{K}{2 m_u m_c} (J(J+1) - s(s+1) - \frac{3}{4}) \end{equation*}$$

But I can't derive this exact result.

My process has been:

-Express the product of spin operators as:

$$\begin{equation*} \vec{S_i}\vec{S_j} = \frac{1}{2} [(S_{ij})^2 - S_i^2 - S_j^2] \end{equation*}$$

Use that: $$\begin{equation*} S_{ii}^2 = s(s+1) (eigenvalue) \end{equation*}$$ $$\begin{equation*} S_{i}^2 = \frac{3}{4} (eigenvalue) \end{equation*}$$ $$\begin{equation*} J^2 = S_{uuc}^2 = S_{uc}^2 + S_c^2 + 2 S_{uc}S_u \end{equation*}$$

$$\begin{equation*} J^2 = J(J+1) (eigenvalue) \end{equation*}$$

-And getting:

$$\begin{equation*} H_{ss} =\frac{K}{2 m_u^2}(s(s+1) - \frac{3}{2}) + \frac{K}{2 m_u m_c} (J(J+1) - s(s+1) - 2S_{uc}S_u - \frac{3}{2}) \end{equation*}$$

So the problem seems to be the term: $$\begin{equation*} - 2S_{uc}S_u \end{equation*}$$

How do I compute it? Am I doing something wrong? (other than just substituting eigenvalues as if they were equal to their operators, I hope it's understandable).

Assuming you map cuu to i =1,2,3, and inserting eigenvalues where appropriate, you have $$j(j+1)=\vec J ^2= (\vec S_1+\vec S_2+\vec S_3)^2= 9/4+ 2(\vec S_1\cdot \vec S_2+ \vec S_1\cdot \vec S_3+\vec S_2\cdot \vec S_3).$$ You also appear to be defining s as the spin of the uu diquark, $$2\vec S_2\cdot \vec S_3= s(s+1) -3/2,$$ so that $$2(\vec S_1\cdot \vec S_2+ \vec S_1\cdot \vec S_3)= j(j+1) -9/4 +3/2-s(s+1).$$
Substituting these two into your degeneracy-lifting hamiltonian, $$H_{ss} =\frac{K}{2 m_u^2}\left ( s(s+1) - \frac{3}{2}\right ) + \frac{K}{2 m_u m_c} \left ( j(j+1) - s(s+1) - \frac{3}{4}\right )~.$$